Effect of daphnetin combined with tobramycin on Pseudomonas aeruginosa biofilm infection in vitro and in vivo - Dingbin Li; Chao Mao; Siyuan Chen; Zhongwei Wang; Weilin Zhang; Zhencong Li; Liangsheng Li; Chaoqin He; Weixiong Guo; Jinsong Wei; Qingjun Wei (Frontiers in Immunology)
ObjectiveThe aim of this study was to investigate the effectiveness of daphnetin in combination with tobramycin on Pseudomonas aeruginosa biofilm infection in vitro and in vivo.MethodThe study was divided into four groups: control, tobramycin, daphnetin, and tobramycin combined with daphnetin groups. First, a 72-h Pseudomonas aeruginosa biofilm model was established in vitro. The antibacterial effects of daphnetin and tobramycin alone and in combination were evaluated using various methods, including microdilution, crystal violet staining, colony counting, and electron microscopy. Then, a model of Pseudomonas aeruginosa biofilm infection in rabbit joints was established in vivo. After 7 days of continuous treatment, the rabbits were sacrificed on day 14 post infection. The therapeutic effect of daphnetin and/or tobramycin was further evaluated by observing the gross anatomy of the knee joint, biofilm PNA-FISH, synovial bacterial load, and pathology.ResultsThe results showed that daphnetin had a minimum inhibition concentration (MIC) of 890 µg/mL against the PAO1 strain, while tobramycin had an MIC of 2.75 µg/mL against the same strain. Crystal violet staining and colony counting showed that the biofilm in the group treated with both daphnetin and tobramycin was significantly less than that in the control group (P < 0.05). Scanning electron microscopy further confirmed that the combination of daphnetin and tobramycin had the strongest bactericidal effect. In vivo, the knee joint of rabbits in the daphnetin combined with tobramycin group had the least gross anatomical inflammatory response, amount of PNA-FISH biofilm, synovial colony count, synovial pathological examination of inflammatory cell infiltration, and synovial thickening.ConclusionThe study indicated that daphnetin may be a promising synergist that enhances the activity of tobramycin against Pseudomonas aeruginosa biofilm infection in vitro and in vivo.